The False Prince : The Ascendance Trilogy #1 - Nielsen, Jennifer A. (New York : Scholastic, 2013)
In the country of Carthya, a devious nobleman engages four orphans in a brutal competition to be selected to impersonate the king's long-missing son in an effort to avoid a civil war.
Reprint. Originally published: 2012.
Keywords: Impersonation -- Fiction; Princes -- Fiction; Orphans -- Fiction; Courts and courtiers -- Fiction; Secrets -- Fiction; Imposters and imposture -- Fiction; Princes -- Fiction; Orphans -- Fiction; Courts and courtiers -- Fiction; Secrecy -- Fiction